Meningkatkan Kerjasama Peserta Didik dan Hasil Belajar IPAS Kelas IV melalui Model Pembelajaran STAD di Sekolah Dasar - Dewi, Febriyanti Sari; Widyasari, Choiriyah (FONDATIA, 2024)
In 21st-century learning, collaborative skills are essential for effective education. Collaboration inherently leads to improved student learning outcomes. To enhance collaboration and learning results, appropriate instructional models are necessary. This study aims to improve collaboration and learning outcomes in the subject of IPAS for fourth-grade students using the STAD (Student Teams Achievement Division) cooperative learning model. The subjects were 27 students from grade IV at SD Muhammadiyah 23 Semanggi, Surakarta, comprising 17 males and 10 females. The research employed the Classroom Action Research (CAR) method, conducted over two cycles, involving planning, implementation, observation, and reflection in each cycle. Data were collected through observation sheets on the learning process, cooperation, and tests. Quantitative descriptive analysis was applied to the data. Results indicate a notable improvement in student collaboration, rising from 70.36% in Cycle I to 82.03% in Cycle II, reflecting an 11.67% increase. Learning outcomes also improved significantly, with pre-cycle average scores at 56.30 and only 14.81% of students achieving proficiency. By Cycle I, the average score increased to 76.30, with 66.67% of students achieving proficiency. In Cycle II, the average score further rose to 82.96, with 81.48% of students achieving proficiency. Based on the data analysis, it can be concluded that the implementation of the STAD cooperative learning model enbances both collaboration and learning outcomes in IPAS for fourth-grade students in elementary school.